The what, why, and how of spirituality in the workplace revisited: a 14-year update and extension. Issue 3 (2nd July 2016) - Houghton, Jeffery D.; Neck, Christopher P.; Krishnakumar, Sukumarakurup
ABSTRACT: Over the past two decades, conceptual and empirical research on the concept of workplace spirituality has increased and expanded significantly. An early and influential article by Krishnakumar and Neck (2002, Journal of Managerial Psychology 17 (3): 153–164) helped provide direction and structure to the nascent field of workplace spirituality by examining the "what" – the definitions and meanings of multiple views of workplace spirituality, the "why" – the potential benefits for organizations from encouraging such differing views of workplace spirituality among their members, and the "how" – the ways in which spirituality may be encouraged or implemented within organizations. The current paper provides a retrospective update and extension of the Krishnakumar and Neck (2002 ) "what, why, and how" framework and "spiritual freedom" model. More specifically, the paper reviews the development and expansion of the workplace spirituality literature over the past decade and a half and considers the potential contributions of a number of contemporary leadership approaches including self-leadership, shared leadership, and authentic leadership to spirituality in the workplace. The paper concludes with an examination of key directions for future research in the workplace spirituality domain.